Evaluation of the potential efficiency of activated carbons produced from biomass for ibuprofen and amoxicillin removal from water by adsorption (2012)
Pineapple peels (PP) and mango pits outer husk (MP) were used to manufacture granular AC by direct activation with steam. Activated carbon from pineapple peels (ACPP) and activated carbon from mango pits (ACMP) with an apparent surface area of 921 and 999 m2/g respectively were obtained. Results from pHpzc revealed basic character in the surface of both activated carbons. These carbons were tested and compared with a commercial activated carbon (GAC) for ibuprofen (IBU) and amoxicillin (AMOX) adsorption from water. Kinetic adsorption data showed that the process obeyed pseudo-second order kinetic equation for all ACs. ACPP and ACMP reached equilibrium at 24 h for both molecules; however, GAC needed barely 48 h to reach saturation. Equilibrium data exhibited that adsorption of IBU on ACs is of Freundlich type. Adsorption of AMOX on ACPP and ACMP was better described by Freundlich model but adsorption on GAC is of Langmuir type. In addition, performance of ACs showed that GAC is the most efficient in IBU adsorption but ACMP is superior in AMOX adsorption from water.